Peran Program Karawang Berseri dalam Upaya Pemberdayaan Masyarakat, Pencegahan dan Penanganan Kekerasan Terhadap Perempuan dan Anak - Wazirul Luthfi; Iftitahur Rohmah; Diaz Alvin Firdausa; Annisa Nur Fadhillah (Syntax Corporation Indonesia, 2023)
The increased recognition of the significance of sustainable development has led business communities in Indonesia to fulfill Corporate Social Responsibility (CSR). One example is the implementation of a corporate social responsibility program by PT Pertamina EP Zone 7 Tambun Field which focuses on efforts to eradicate violence against women and children in Karawang, known as